2015
DOI: 10.1007/s00266-015-0454-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Media and Easily Accessible Online Information on the Aesthetic Plastic Surgery Practice: Literature Review and Our Own Experience

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(151 citation statements)
references
References 20 publications
2
130
0
10
Order By: Relevance
“…19 However, social networking sites can and have been used to evaluate many aspects of health care and plastic surgery, including evaluating facial attractiveness, measuring acceptance of cosmetic surgery, and reviewing impact of social media use on plastic surgery practice. 11, 16, 2022 However, the use of social media to evaluate outcomes in plastic surgery is limited, and to our knowledge this is the first such study for evaluating migraine surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 However, social networking sites can and have been used to evaluate many aspects of health care and plastic surgery, including evaluating facial attractiveness, measuring acceptance of cosmetic surgery, and reviewing impact of social media use on plastic surgery practice. 11, 16, 2022 However, the use of social media to evaluate outcomes in plastic surgery is limited, and to our knowledge this is the first such study for evaluating migraine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Montemurro et al 11 report that worldwide, 95% of patients turn to the Internet for information before having a consultation with a plastic surgeon, and almost half of these use social media as their primary source of information. In the present study, we found that patients with migraines are using Facebook to share perceptions and outcomes of their surgical treatment and specifically, 90% recommend nerve surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakar pembedahan plastik didapati banyak menggunakan media sosial untuk menyebarkan maklumat mengenai pembedahan plastik kerana ia dilihat sebagai alat pemasaran yang berkesan untuk meningkatkan pendedahan khalayak terhadap pembedahan plastik. Montemurro et al (2015) yang menjalankan kajian literatur terhadap pengaruh media sosial dan internet terhadap pembedahan plastik mendapati bahawa majoriti kajian-kajian lepas mengakui bahawa media sosial memainkan peranan penting dalam mempengaruhi persepsi dan tingkah laku terhadap pembedahan plastik. Khalayak didapati lebih bergantung kepada maklumat mengenai pembedahan plastik dalam talian dan lebih cenderung untuk 265 E-ISSN: 2289-1528 https://doi.org/10.17576/JKMJC-2017-3301-18 mendapatkan nasihat melalui media sosial.…”
Section: Pengenalanunclassified
“…This heavy focus on DTC marketing for specifically prescription drugs can be traced to changes in regulations during the 1990s, which made the United States one of the only two Western nations in the world besides New Zealand where DTC advertising for prescription drugs is allowed. There is also a growing literature on DTC marketing for cosmetic surgery (Montemurro, Porcnik, Hedén, & Otte, 2015;Tait, 2007), with the empirical research focusing in particular on the potential effects of exposure on body image (Sperry, Thompson, Sarwer, & Cash, 2009) and intention to undergo cosmetic surgery (Nabi, 2009). …”
mentioning
confidence: 99%